The predictive ability of emotional representation and self- satisfaction among the students of the upper basic stage of the Syrian refugees in the schools of the Directorate of Education of the Giza District - Al- Samor, Salah Sanad (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to reveal the level of both emotional representation and self- contentment among students of the upper basic stage of Syrian refugees in the schools of the Directorate of Education of the Giza District, and to identify the nature of the relationship between emotional representation and self- contentment, and to determine the possibility of predicting the level of self- contentment through the level of emotional representation. The study used the descriptive analytical method, and the study sample consisted of (185) male and female students, who were chosen by random method, and two scales were applied to them, namely the emotional representation scale and the self- contentment scale, and the study concluded that there is an average level of emotional representation and self- contentment among students, and a positive relationship between emotional representation and self- contentment among students. Differences in emotional representation due to gender and in favor of females, while it was found that there were no differences in subjective contentment due to gender.
Keywords: predictive ability; emotional representation; self- contentment; upper basic stage students; Syrian refugees